North-eastern range extension of the anemone Stichodactyla haddoni to the Marshall Islands represents a new record of host use by the endemic anemonefish Amphiprion tricinctus - Hobbs, Jean-Paul; Beger, M.; de Brauwer, M.; Emslie, M. (Cambridge University Press, 2014)
Amphiprion tricinctus is an anemonefish endemic to the Marshall Islands that was previously reported to inhabit four species of sea anemone. Underwater visual surveys in 2009 and 2010 located five individuals of the anemone Stichodactyla haddoni in the shallow lagoon of Majuro Atoll. This is the first record of S. haddoni in the Marshall Islands and a significant north-eastern range extension by 2200 km from its nearest record in Chuuk State, Federated States of Micronesia. Stichodactyla haddoni was inhabited by juvenile and adult A. tricinctus. This report is the first todescribe a symbiotic relationship between A tricinctus and S. haddoni. The number of host anemone species inhabited by A. tricinctus now extends to five.